Complexity, ambiguity, and the boundaries of the future: Toward a reflexive scenario practice in sustainability science - Lazurko, Anita (University of Waterloo, 2023)
The future of humanity and the biosphere is complex and increasingly uncertain, complicating efforts to understand and address 21st century environmental crises like biodiversity loss and climate change. Transdisciplinary scenario practice offers a promising avenue to make sense of this complexity and uncertainty. Scenarios are often defined as coherent, internally consistent, and plausible descriptions of the potential future trajectories of a system, and transdisciplinarity is an integrative, problem-oriented, and societally embedded research paradigm that aims to generate knowledge about complex and contested problems. However, despite its promise, transdisciplinary scenario practice grapples with persistent ambiguity (i.e., the existence of multiple valid frames), which emerges from the plural values and perspectives of diverse actors involved in knowledge production, resistance to integration via any singular frame offered by an individual discipline, and the inherent complexity of sustainability challenges. The lack of concepts, frameworks, and tools to operationalize ambiguity presents risks to the salience and legitimacy of transdisciplinary scenario practice. Ambiguity renders any scenario process as a partial framing of the future that focuses attention on what is most relevant and is contingent on how it was produced. Reflexivity (i.e., the process of examining how one’s own beliefs, judgments, and practices influence the research) is cited as a crucial capacity for navigating such ambiguity, yet its role in sustainability science, and in scenario practice, remains unclear. Without reflexivity, those developing and using the scenarios are left without the means or motivation to critically reflect on how the scenarios are produced, their underlying assumptions, and their strengths and limitations for different modes of application. Further, the boundaries that delineate what future conditions and values are included and excluded from the scenarios are rendered invisible. This gap influences the salience and legitimacy of the scenarios to real-world sustainability challenges, particularly amid contemporary demands to enrich scenarios with the novel and potentially transformative conditions of the 21st century. This dissertation explores two opportunities to operationalize ambiguity through reflexivity in transdisciplinary scenario practice. First, the field of operational research has a multi-decade history grappling with theoretical and practical aspects of ambiguity through critical systems thinking (CST), offering opportunities for sustainability science. Second, most scenario methods require implicit trade-offs that reduce or ignore aspects of complexity (and thus ambiguity), failing to get the “big picture” roughly right. Semi-quantitative scenario methods like cross-impact balances (CIB) produce internally consistent scenarios by systematically and reflexively integrating diverse drivers of change, thereby reconciling some of these trade-offs and offering a promising yet underutilized scenario method for sustainability science. Paper I aimed to contribute to reflexive scenario practice in sustainability science by making ambiguity explicit and operational using the lens of CST. This investigation generated the Boundaries of the Future framework, a novel synthesis of literatures that characterizes how key boundary judgments (i.e., choices that delineate what is included or excluded from a system) involved in the design of a scenario process influence the scope of future potential (i.e., future conditions and values) reflected in scenario outcomes, and proposes the degree to which this scope of future potential may reflect the dynamics of, and/or conditions for, social-ecological systems (SES) change (i.e., a dominant complexity-based lens that views high-level system behavior as emerging from social-ecological and cross-scale interactions and feedbacks). The most expansive choice under each of the ten boundary judgments in the framework enriches scenarios with the conditions for transformation (i.e., fundamental, systemic shifts away from existing systems; desirable or undesirable; navigated or unintended). The framework can be operationalized as an ex ante or ex post reflexive tool in sustainability research and practice by rendering each of the ten boundary judgments as an explicit site of critical reflection in a scenario process. Doing so can improve the salience and legitimacy of the scenarios, including by enriching scenarios with the potential for transformation. Paper II aimed to explore the potential for semi-quantitative scenario methods to enrich scenario practice for a) the development of ‘big picture’ (i.e., integrative and holistic) scenarios in sustainability science and b) river basins attempting to build resilience to climate change. This objective was addressed through a case study transdisciplinary CIB modelling process in the Red River Basin, a transboundary river basin shared by the United States and Canada. The scenarios explore ‘big picture’ scenarios of a river basin under climate change by characterizing future change as emergent from interactions between diverse efforts to build resilience and a complex, cross-scale SES. The results surface significant complexities and ambiguities surrounding efforts to build resilience in river basins and affirm the potential for the CIB method to generate unique insights about the trajectory of SESs. Reflections on the irreducible ambiguity that persisted through Papers I and II led to the development of Paper III, which aimed to explore how key concepts, frameworks, and lessons from CST may be adapted to help address the challenges presented by ambiguity in sustainability science (i.e., beyond scenario practice). The major contribution of this investigation is an operational definition of ambiguity focused on the subjectivity of system boundaries (i.e., an emergent feature of the simultaneous and interacting boundary processes associated with being, knowing, and intervening in complex systems) and two recommendations for sustainability scientists to operationalize ambiguity as a valuable means of addressing sustainability challenges: 1) adjust the theoretical orientation of sustainability science to consider the potential for and consequences of theoretical incommensurability and discordant pluralism, and 2) nurture the reflexive capacities of transdisciplinary researchers to navigate persistent ambiguity. CST literature and four case study reflections (including the transdisciplinary scenario process from Paper II) were used to develop the novel framework of Reflexive Boundary Critique to guide critical reflection on ambiguity at all stages of the research process. In sum, this dissertation explored opportunities to operationalize ambiguity through reflexivity in transdisciplinary scenario practice, contributing to a rich and growing body of research that addresses the ambiguities inherent to research about complex sustainability challenges. My hope is that this contribution helps sustainability scientists give shape to and embrace ambiguity as a fundamental part of rigorous sustainability science.
Keywords: scenarios; sustainability science; social-ecological systems; reflexivity; boundaries; critical systems thinking; ambiguity; cross-impact balances; transformation; transdisciplinarity